2022
DOI: 10.3390/children9060780
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Health-Related Quality of Life in German Adolescents after the Third Wave of the COVID-19 Pandemic

Abstract: Evaluations after the first and second waves of the COVID-19 pandemic in Germany showed an increase in mental health problems and a reduction in health-related quality of life (HRQoL). The aim of the study was to assess those aspects after the third wave of COVID-19 in adolescents who decided to receive a vaccination. In students aged 12–17 years recruited from schools in one German region, mental health (by the strengths and difficulties questionnaire, SDQ) and HRQoL (by KIDSCREEN-10) were assessed by both a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 32 publications
(46 reference statements)
3
12
0
Order By: Relevance
“…Sex and age were found to be positive predictors of the HRQoL. In this study, similarly to previous findings, the boys [ 21 , 39 , 40 , 41 , 42 , 43 , 44 ] and the younger adolescents [ 39 , 42 , 44 , 45 , 46 ] had a better HRQoL. We expected these findings as sex and age differences in the health-related quality of life are confirmed and could be connected to puberty with all the biological, emotional, and social changes that occur during this period.…”
Section: Discussionsupporting
confidence: 90%
“…Sex and age were found to be positive predictors of the HRQoL. In this study, similarly to previous findings, the boys [ 21 , 39 , 40 , 41 , 42 , 43 , 44 ] and the younger adolescents [ 39 , 42 , 44 , 45 , 46 ] had a better HRQoL. We expected these findings as sex and age differences in the health-related quality of life are confirmed and could be connected to puberty with all the biological, emotional, and social changes that occur during this period.…”
Section: Discussionsupporting
confidence: 90%
“…However, HRQoL differed across time points as well as strata of sex and age, with older girls more frequently reporting low HRQoL compared to boys of both age groups and younger girls. This observation with respect to age and sex is in line with other studies [4,39,40] and has been reported prior to the COVID-19 pandemic [22]. Hypotheses about the causal mechanisms behind these differences include complex interactions of socio-behavioral and societal factors [41] and must be investigated further [40,42].…”
Section: Discussionsupporting
confidence: 90%
“…The present study took place during summer 2021 when pandemic-related restrictions were loosened and schools mostly open. Students in the study reported higher levels of HRQoL compared with results from other studies at earlier pandemic time points [40], which could be attributed to the easing of restrictions having a positive impact [4,39,44]. In June 2021 (T1), Berlin school students generally resumed classes with regular class sizes.…”
Section: Discussionmentioning
confidence: 68%
“…Barbieri et al observed that the proportion of children in South Tyrol with low HRQoL was higher in girls compared to boys (38 vs. 28%) ( 41 ). Another recent study from Germany also reported such age and gender differences ( 43 ). However, these findings are not surprising.…”
Section: Discussionmentioning
confidence: 79%